Late-life Depression, Suicidal Ideation, and Attempted Suicide: The Role of Individual Differences in Maximizing, Regret, and Negative Decision Outcomes - de Bruin, Wändi Bruine (J Behav Decis Mak, 2015)
Suicide rates are highest in adults of middle and older age. Research with psychiatric patients has shown that proneness to feel regret about past decisions can grow so intense that suicide becomes a tempting escape. Here, we examine the additional role of individual differences in maximizing, or the tendency to strive for the best decision, rather than one that is good enough. We provided individual-differences measures of maximizing, regret proneness, and negative life decision outcomes (as reported on the Decision Outcome Inventory or DOI) to a non-psychiatric control group, as well as three groups of psychiatric patients in treatment for suicide attempts, suicidal ideation, or non-suicidal depression. We found that scores on the three individual-differences measures were worse for psychiatric patients than for non-psychiatric controls, and were correlated to clinical assessments of depression, hopelessness, and suicidal ideation. More importantly, maximizing was associated with these clinical assessments, even after taking into account maximizers’ worse life decision outcomes. Regret proneness significantly mediated those relationships, suggesting that maximizers could be at risk for clinical depression because of their proneness to regret. We discuss the theoretical relevance of our findings and their promise for clinical practice. Ultimately, late-life depression and suicidal ideation may be treated with interventions that promote better decision making and regret regulation.